MicroRNA expression profile of chicken jejunum in different time points Eimeria maxima infection - Jebessa, Endashaw; Bello, S.F.; Guo, L.; Tuli, M.D.; Hanotte, Olivier H.; Nie, Q. (Frontiers Media, 2024)
Coccidiosis stands as a protozoan disease of notable economic impact, characterized by an intracellular parasite that exerts substantial influence over poultry production. This invasion disrupts the integrity of the enteric mucosa, leading to the emergence of severe lesions and diminishing the efficiency of feed utilization in chickens. MicroRNA (miRNA) are short, non-coding RNA molecules with approximately 21–24 nucleotides long in size that play essential roles in various infectious diseases and inflammatory responses. However, the miRNA’s expression patterns and roles in the context of Eimeria maxima infection of chicken intestines remain unclear. miRNA sequencing was employed to assess the miRNA expression profile in chicken jejunum during E. maxima infection. In this study, we analyzed miRNA expression profiles related to the host’s immune response in the chicken jejunum during E. maxima infection. At 4 days infection and control (J4I versus J4C), 21 differentially expressed miRNAs in the jejunum were identified, comprising 9 upregulated and 12 downregulated miRNAs. Furthermore, in the jejunum, at 7 days infection and control (J7I versus J7C) groups, a total of 35 significantly differentially expressed miRNAs were observed, with 13 upregulated and 22 downregulated miRNAs. The regulatory networks were constructed between differentially expressed miRNA and mRNAs to offer insight into the interaction mechanisms between chickens and E. maxima coccidian infection. Furthermore, within the comparison group, we obtained 946, 897, and 281 GO terms that exhibited significant enrichment associated with host immunity in the following scenarios, J4I vs. J4C, J7I vs. J7C, and J4I vs. J7I, respectively. The KEGG pathway analysis indicated notable enrichment of differentially expressed miRNAs in the jejunum, particularly in J4I vs. J4C; enriched pathways included metabolic pathways, endocytosis, MAPK signaling pathway, regulation of actin cytoskeleton, and cytokine–cytokine receptor interaction. Moreover, in J7I vs. J7C, the KEGG pathway was significantly enriched, including metabolic pathways, protein processing in the endoplasmic reticulum, ubiquitin-mediated proteolysis, and FoxO signaling pathway. A comprehensive understanding of the host genetic basis of resistance with a combination of time-dependent infection to the Eimeria parasite is crucial for pinpointing resistance biomarkers for poultry production.